ViralVCD: tracing information-diffusion paths with low cost media in developing communities - Sambasivan, Nithya; Cutrell, Edward; Toyama, Kentaro; Cutrell, Ed (CHI '10: Proceedings of the 28th international conference on Human factors in computing systems, 2010)
We describe ViralVCD: a low cost method for tracing paths of information diffusion in developing communities using physical media. We instituted a participatory video framework for creation and dissemination of developmental videos in seven urban slums and peri-urban communities of Bangalore, India. By combining a call-in contest with Video CDs, we were able to measure developmental impact as well as elicit data on social networks and technology usage practices. In particular, our technique was able to extract data from multiple layers—social, technological, and developmental. ViralVCD allowed us to identify key actors and map information diffusion, as well as technology ownership and access. These findings have implications for HCI initiatives targeting low income locales and populations.